Fair trade in insurance industry: Premium determination of Taiwan automobile insurance - Vanezian, Emilio; Li, Chu-Shiu; Liu, Chwen-Chi; Yu, Chin-Ping (2007)
This paper examines premium determination of voluntary automobile insurance policy and risk classification under a heavily regulated rating system in Taiwan. We investigate the distribution of actual premium and pure premium, based on unique data to test if premium reflect appropriate gender-age factor. The reasonableness of loading and the difference in driving exposure between policyholder and driver are investigated for three different types of policy. An adjustment of gender-age premium coefficients is called for.